Nexo causal entre la complejidad económica y la desigualdad de ingresos en América Latina: el rol del capital humano y la concentración urbana - Armijos Avila, Ximena Natal (2022)
The increase in income inequality generates negative effects that are usually associated with high levels of poverty and failed development processes. The objective of this research is to examine the causal relationship between economic complexity, human capital, urban concentration and income inequality for 17 Latin American countries in the period 1980-2019, a region with the highest level of inequality worldwide. For this purpose, Westerlund's (2007) cointegration method, ARDL dynamic models and Dumistrescu and Hurlin's (2012) test were used; to determine the short-run, long-run and causality relationship between the variables. The contribution of the research is to contribute with empirical evidence through a new model that has not been previously estimated for the region. The empirical results indicate a long-term relationship between economic complexity, human capital, urbanization and income inequality at the GLOBAL, PIA and PIMA levels. In addition, there was evidence of bidirectional causality between economic complexity and income inequality, and unidirectional causality indicating that urbanization causes income inequality for the PIMB group. A possible policy implication derived from the research is to improve the quality of education through structural changes in education.